Polysaccharide Transglycosylases: A Survey of Assay Methods - Farkaš, Vladimír; Vadinová, Kristína; Stratilová, Eva (Journal of Plant Cell Development, 2018)
Polysaccharide transglycosylases (PTGs) are a unique group of glycoside hydrolases playing important roles in the formation and modification of plant and fungal cell walls. Their action involves cutting the molecule of the polysaccharide substrate at the glycosidic bond, followed by transfer of the newly formed reducing-end fragment to the non-reducing end of another polysaccharide molecule, with the formation of a new glycosidic bond. As there is no net increase in the number of reducing ends in the system, conventional reductometric methods used to assess the activity of glycoside hydrolases are ineffective. Since the PTGs participate in vital processes, such as the elaboration of cell walls in plants and fungi, and are not present in animal cells, they are considered as possible targets for future specific fungicides and herbicides. Biochemical studies of PTGs, as well as the search for their inhibitors, require the availability of convenient and efficient methods for their assay. In this review we briefly describe the principles of methods used to detect and to determine the activity of this important group of enzymes.
Keywords: polysaccharides; transglycosylation; assay; high-throughput; cell walls